2021
DOI: 10.1038/s41467-021-24706-4
|View full text |Cite
|
Sign up to set email alerts
|

Ternary aromatic and anti-aromatic clusters derived from the hypho species [Sn2Sb5]3−

Abstract: Heterometallic clusters have attracted broad interests in the synthetic chemistry due to their various coordination modes and potential applications in heterogeneous catalysis. Here we report the synthesis, experimental, and theoretical characterizations of four ternary clusters ([M2(CO)6Sn2Sb5]3− (M = Cr, Mo), and [(MSn2Sb5)2]4−, (M = Cu, Ag)) in the process of capturing the hypho- [Sn2Sb5]3− in ethylenediamine (en) solution. We show that the coordination of the binary anion to transition-metal ions or fragme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 73 publications
(54 reference statements)
1
16
0
Order By: Relevance
“…Previously, AdNDP has been shown to be a very efficient and visual approach for the interpretation of the molecular orbital-based wave functions for various systems with complex bonding patterns. [41][42][43] AdNDP was reported to be qualitatively insensitive to the level of theory used. [41,43,44] Specifically, it was found that as long as the basis set is large enough to sufficiently describe electronic structure, AdNDP showed no qualitative dependency on the basis set.…”
Section: Synthesis Of [K(222-crypt)]mentioning
confidence: 99%
“…Previously, AdNDP has been shown to be a very efficient and visual approach for the interpretation of the molecular orbital-based wave functions for various systems with complex bonding patterns. [41][42][43] AdNDP was reported to be qualitatively insensitive to the level of theory used. [41,43,44] Specifically, it was found that as long as the basis set is large enough to sufficiently describe electronic structure, AdNDP showed no qualitative dependency on the basis set.…”
Section: Synthesis Of [K(222-crypt)]mentioning
confidence: 99%
“…Upon addition of ZnPh 2 to such extractions, a complex of a corresponding 2 : 5 anion was obtained, [(ZnPh) 2 (Sn 2 Sb 5 )] 3− [8] . A partially oxidized version of this binary anion, “(Sn 2 Sb 5 ) 3− ”, was captured recently in transition metal complexes like [{Mo(CO) 3 } 2 (Sn 2 Sb 5 )] 3− [35] …”
Section: Resultsmentioning
confidence: 99%
“…[8] A partially oxidized version of this binary anion, "(Sn 2 Sb 5 ) 3À ", was captured recently in transition metal complexes like [{Mo-(CO) 3 } 2 (Sn 2 Sb 5 )] 3À . [35]…”
Section: Forschungsartikelmentioning
confidence: 99%
“…Our understanding of the mechanism of growth of these clusters from smaller component parts remains limited, although a small number of recent studies have begun to address this critical issue using a combination of X-ray crystallography, mass spectrometry, and computational analysis. 17,18 In the formation of the group-5 metal clusters [TaGe 8 As 4 ] 3− and [TaGe 8 As 6 ] 3− , for example, fusion of the known tetrahedral [Ge 2 As 2 ] 2− unit with the (unknown) Ta-containing fragments [TaGe 3 ] − and [Ta-Ge 4 As 2 ] − has been shown to provide a viable route to the isolated products. 17 The growth of even larger clusters containing multiple deltahedral units and/or transition metals, which offers the potential for a much wider range of M/E ratios along with the possibility of metal−metal bonding, presents a substantial synthetic challenge simply because the individual building blocks such as the ones shown in Figure 1 typically carry high negative charges.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The crystalline products are often highly sensitive to both air and moisture, but nevertheless a now extensive family of clusters with stoichiometries MPb 9–12 has been synthesized in this way, including [CuPb 9 ] 3– , [NiPb 10 ] 2– , [AgPb 11 ] 3– , [MPb 12 ] n − (M = Au, Ni, Pd, Pt, Co, Rh, Ir, Mn), and [(Cp*Ru)­CuPb 11 ] 2– (Figure ). Our understanding of the mechanism of growth of these clusters from smaller component parts remains limited, although a small number of recent studies have begun to address this critical issue using a combination of X-ray crystallography, mass spectrometry, and computational analysis. , In the formation of the group-5 metal clusters [TaGe 8 As 4 ] 3– and [TaGe 8 As 6 ] 3– , for example, fusion of the known tetrahedral [Ge 2 As 2 ] 2– unit with the (unknown) Ta-containing fragments [TaGe 3 ] − and [TaGe 4 As 2 ] − has been shown to provide a viable route to the isolated products …”
Section: Introductionmentioning
confidence: 99%